Model Keteladanan Pengelolaan Pendidikan Islam K.H. Hasyim Asy’ari - Suhada, Suhada; Fauzi, Anis; Firdaos, Rijal (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 24 No 2 (2024)DO - 10.24843/PJIIB.2024.v24.i02.p02, 2024)
This article aims to explain the meaning of Islamic education and explain the intellectual impact of K.H. Hasyim Asy’ari on the implementation of Islamic education. The research methodology used in this research is library research, which includes reading, writing and analyzing research materials, as well as utilizing library-centered information collection strategies. The author uses content analysis as a method for analyzing data in this research. Content analysis is used to compare the findings of a study with other studies related to the same issue. Textbooks and journal articles serve as sources of knowledge used to prepare this article. The research problem revolves around two key questions: "What is the definition of Islamic education proposed by K.H. Hasyim Asy’ari?" and "What is the specific intellectual impact of K.H. Hasyim Asy’ari on the progress of contemporary Islamic education?". The findings of this research explain that K.H. Hasyim Asy’ari's ideas regarding the conceptualization of Islamic education as found in the book Adabul 'Alim Wal Muta'alim and the impact of K.H. Hasyim Asy’ari's ideas on the implementation of Islamic education can be found in the formulation of Law no. 20 of 2003 concerning the Indonesian national education system.